FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN MENJALANI TERAPI HEMODIALISA PADA PASIEN GAGAL GINJAL KRONIK DI RSU. ROYAL - eva latifah nurhayati (Jurnal Maternitas Kebidanan, 2019)
Obodience is one of the problem factors in hemodialysis patients who experience chronic kidney disese. Noncompliance can lead to therapiutic failur thereby decreasing the patient’s quality of life,increasing mortality and morbidity. The severy of renal impairment determines the type of treatment and treatment given. In some cases, damage to kidney failur and circulation can be prevented by taking medication to control blood pressure and control blood cholesterol levels. At least 1 out of 100 people with kidney stroke will have kidney failur. People with chronic renal failur require furtur treatment to replace a number of kidney functions such as performing hemodialysis. The purpose of this study was to determine the factor associated with hepatitis undergoing hemodyalis in patien with chronic renal failure in Royal prima hospital, patient with chronic renal failur who undergo hemodyalisis in royal prima hospital 114 patients in september.The type of research used is analytic with cross sctional design. The population of 114 respondents and the sample is 29 respondents. Sampling technique in this research is by perposive sampling technique. Data is processed and analyzed by Chi-square test. Data colection method by filling queationer.Based on the result of this research,there is a significant corelation between adherence with motivation (p=0,069), age (p=0,002), family support (p= 0,002). The concclusion of this research is that there is connection between the faktors associated with our live hemodialisa in patients with kidney failur in patients with kidney failur in royal prima hospital in 2018.